Sorption and mechanical properties of natural rubber vulcanizates in aqueous media - Ananoria, Abhel Y.
Vulcanized natural rubber is an important polymeric material used in many industrial and engineering applications. However, the sorption of solvent penetrants into the rubber may cause deterioration during service which could translate to added maintenance cost and most importantly safety hazard. To investigate their sorption and mechanical properties, vulcanized natural rubber compounds immersed in water, H2SO4, and NaOH solutions were studied as function fo ingredient loading and solution concentration using gravimetric method at 80°C. Rubber sheets were compounded according to a fractional factorial design of experiment, where ingrediens are treated as factors varied at two levels of loading. Sorption properties such as maximum uptake and uptake rates were determined from the sorption curves. ANOVA shows that high loadings of sulfur, asphalt, and used oil significantly increase sorption properties while high loadings of reclaimed rubber, CaCO3, MBT, and MBTS significantly decrease the measured sorption properties in water and NaOH. On the other hand, increased loading of sulfur, CaCO3, kaolin clay and reclaimed rubber increase sorption properties while used oil and DPG decrease the measured sorption properties in H2SO4. Higher concentrations increase the sorption properties in H2SO4 while the contrary is true in NaOH solution. Desorption kinetics follow Fickian diffusion.